On oxidation behaviour of platinum aluminide coated nickel based superalloy CMSX-(4) - Reed, R; Wu, RT; Hook, MS; Rae, C; Wing, R (2009)
The effects of platinum modification on the isothermal oxidation performance of a chemical vapour deposition aluminide coating are examined. Platinum was electrodeposited to varying thicknesses (to a maximum of 16 μm) onto the CMSX-4 single crystal superalloy, before applying a high temperature/low activity aluminisation process. The oxidation performance at 1100°C improved monotonically with increasing Pt thickness; this was confirmed by thermal gravimetric analysis. The degree of rumpling of the alumina scale was also decreased with increasing platinum. The superior oxidation resistance of platinum modified aluminide coatings is a consequence of the β-NiAl formed during aluminisation containing an enhanced Al/Ni ratio, reduced levels of Co and Ti and decreased concentrations of the refractory elements Re, W and Ta. This seems to be due at least in part to the microstructural effects caused by the prior diffusion of platinum into the surface, which causes the generation of a γ-(Ni,Pt)/γ′-(Ni,Pt) 3Al microstructure; the upper portion of the Pt diffused coating comprises predominantly the γ′-(Ni1Pt)3Al phase which is rich in Pt and Al and depleted in Co and the refractory elements W and Re. The ramifications of our findings for the design of bond coats required for thermal barrier coating systems are discussed. © 2009 Institute of Materials, Minerals and Mining.